(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
Phrases play an important part for the acquisition of communicative foreign language skills. At the interface between linguistic science and methodology of teaching, the present paper covers the nature of phrases, their applicability and their integral importance despite existing criticism. A focal point showcasing the sub steps involved with the teaching of phrases considering the capabilities they possess for intercultural understanding to learners of German as a foreign language and as a second language.